Formulation Of a Functional Tea Using Pineapple Peel, Lemon Peel, Mint, And Green Tea - Sheilla Asimire (Uganda Christian University, 2025)
This study addresses the challenges of food waste and nutritional deficiency by creating a functional tea from pineapple peels, lemon peels, mint, and tea. Fruit processing in Uganda generates a substantial amount of organic waste, with pineapple and lemon peels accounting for around 20–35% of the fruit weight which have bioactive compounds. Using response surface methodology with a D-optimal mixture design, 12 experimental formulations were tested, varying proportions of pineapple peel powder, lemon peel powder, and mint, with green tea constant at 30%. Sensory evaluations by 30 panelists assessed appearance, aroma, taste, mouthfeel, and overall acceptability. Results showed that higher pineapple peel powder ratios negatively affected the sensory attributes, while lemon peel powder addition was beneficial for taste and mint addition improved appearance and overall acceptance. The optimized tea blend containing 80% pineapple peel powder, 15% lemon peel powder, and 5% mint showed significantly higher polyphenol content and vitamin C content when compared with the control tea.